A Container with an Insect Corpse: On Essays by Marek Bieńczyk - Czyżak, Agnieszka (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2019)
The article contains considerations on Marek Bieńczyk’s literary output and his book Kontener, published in 2018. All essays from the volume manifest their autobiographical and literary character. The main aim of the paper is to make a diagnosis connected with the particular and common (mis)understanding of the relations between death and life, mourning and vitality, melancholy and literature. This objective is accomplished through essay strategies. In texts that are part of Kontener, the suggestive and expressive subject makes continual new inquiries in order to find the essence of their (Bieńczyk’s) personal, and especially textual, identity.